2017
DOI: 10.28920/dhm47.1.9-16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The ratio deco strategy did not confer any benefit in terms of bubbles but showed the disadvantage of increased decompression-associated secretion of inflammatory chemokines involved in the development of vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Despite the absence of an investigation related to anti-inflammatory mediator changes, these data may be explained considering that SCUBA-related acute inflammation is modulated by circulating WBC and leads to the stimulation of toll-like receptors (TLRs) and, consequently, the activation of NF-κB pathway [37]. Even if the role of anti-inflammatory mediators were not directly investigated in this protocol, it is known that some authors evaluated the inflammatory status measuring IL-6, IL-8, MIP-1β and other pro-inflammatory molecules [38], including chemokines in recreational divers (Spisni, Marabotti et al 2017). Some circulating chemokines, namely CCL2 and CCL5, increased after diving: CC chemokines are stored in and released from PLT and activated LYM [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of an investigation related to anti-inflammatory mediator changes, these data may be explained considering that SCUBA-related acute inflammation is modulated by circulating WBC and leads to the stimulation of toll-like receptors (TLRs) and, consequently, the activation of NF-κB pathway [37]. Even if the role of anti-inflammatory mediators were not directly investigated in this protocol, it is known that some authors evaluated the inflammatory status measuring IL-6, IL-8, MIP-1β and other pro-inflammatory molecules [38], including chemokines in recreational divers (Spisni, Marabotti et al 2017). Some circulating chemokines, namely CCL2 and CCL5, increased after diving: CC chemokines are stored in and released from PLT and activated LYM [39].…”
Section: Discussionmentioning
confidence: 99%
“…Even if the role of anti-inflammatory mediators were not directly investigated in this protocol, it is known that some authors evaluated the inflammatory status measuring IL-6, IL-8, MIP-1β and other pro-inflammatory molecules [38], including chemokines in recreational divers (Spisni, Marabotti et al 2017). Some circulating chemokines, namely CCL2 and CCL5, increased after diving: CC chemokines are stored in and released from PLT and activated LYM [39]. Circulating chemokine CCL5 is known to contribute to endothelial activation and the interaction between endothelial cells and MONO [40].…”
Section: Discussionmentioning
confidence: 99%
“…This study result also consistent with preliminary studies with the object of research in rats, which found an increase in TNFα levels due to decompression diving and also another inflammatory cytokine [7], [26]. In this control group, also in accordance with Spisni et al who stated that the deco-stop strategy provides an advantage in terms of inhibiting gas expansion, but other things show that the deco-stop procedure cannot guarantee that the diver is free from decompression sickness (DCS), this is because there is still an increase in inflammation biomarker secretion, that causes vascular damage, and it seen from biomarkers of C-C motif chemokine ligand-2 (CCL2) and C-C motif chemokine ligand-5 (CCL5) [27].…”
Section: The Effectiveness Of the Pre-dive Treatmentmentioning
confidence: 99%
“…Traditionally, this risk has been attributed to the presence and quantity of decompression bubbles in the blood (vascular gas emboli or VGE) causing blood flow occlusion in various tissues. Recently, DCS has also been associated to the presence of blood microparticles and some symptoms linked to an inflammatory process (Thom et al, 2011; Arieli et al, 2015; Spisni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%